Discovery of New Uracil and Thiouracil Derivatives as Potential HDAC Inhibitors - Omnia R. Elbatrawy; Mohamed Hagras; Moshira A. El Deeb; Fatimah Agili; Maghawry Hegazy; Ahmed A. El-Husseiny; Mahmoud Mohamed Mokhtar; Samy Y. Elkhawaga; Ibrahim H. Eissa; Samar El-Kalyoubi (MDPI AG, 2023)
Background: Histone deacetylase inhibitors (HDACIs) are a relatively new class of potential drugs for treating cancer. Aim: Discovery of new anticancer agents targeting HDAC. Methods: New uracil and thiouracil derivatives panels were designed and synthesized as HDAC inhibitors. The synthesized compounds were tested against MCF-7, HepG2, and HCT-116. HDAC1 and HDAC4 inhibitory activities of these compounds were tested. The most active member was tested for its potential against cell cycle, apoptosis, caspase-3, and caspase-8. Docking studies were carried out against HDAC1. Results: Compounds 5a, 5b, 5f, 5i, 5k, and 5m exhibited promising cytotoxic activities. HDAC1 and HDAC4 inhibitory activities of these compounds were tested. Regarding the HDAC1 inhibitory activity, compound 5m was the most potent member (IC50 = 0.05 µg/mL) compared to trichostatin A (IC50 = 0.0349 µg/mL). For HDAC4, compound 5m showed superior activity (IC50 = 2.83 µg/mL) than trichostatin A (IC50 = 3.349 µg/mL). Compound 5m showed a high potential to arrest the HCT116 cell cycle at the G0-G1 phase. In addition, it showed an almost 17 times apoptotic effect (37.59%) compared to the control cells (2.17%). Furthermore, Compound 5m showed significant increases in the levels of caspase-3 and caspase-8. Finally, the uracil and thiouracil derivatives showed accepted binding mods against HDAC. Conclusions: Compound 5m has potential anticancer activity targeting HDAC with a significant apoptotic effect.